Rancang Bangun Sistem Alarm Pintu Gudang Berbasis Arduino di PT. Sakai Indonesia Bekasi - Muawan Bisri; Okto Kurnia; Arif Maulana (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of technology is currently increasingly rapid in the industrial world, especially in each department there are many tools and spare parts that are very important for company assets, therefore the author designed a warehouse door alarm system to reduce the risk of losing tools and spare parts that aim to protect company assets. In the industrial world, especially at PT. Sakai Indonesia for the doors of each department's room still uses components and types of doors in general, so in this study the author designed a door alarm system tool based on the Arduino Uno microcontroller which aims to reduce the number of spare part losses in the warehouse room. This study uses the prototype method and uses observation, interview, literature and library study methods as data collection methods. The tool designed uses Arduino Nano to receive commands, an infrared sensor device to recognize human movement that breaks it, Arduino Nano to receive commands from sensors that are broken by human movement and send notification SMS. The door alarm system using Arduino Nano is very helpful in increasing awareness of the equipment and spare parts in each department's room.